Synthesis of a Robust Control System with A Reference Model of a Nonlinear Dynamic Object with State Delay (Eurasian Journal of Engineering and Technology, 2023)
In this paper, control problem with a reference model for a nonlinear dynamic object with a delay in state is analyzed and solved. The suggested control algorithm is a special form that links in the opposite direction, where an auxiliary contour and observers are used which is considering all information about the perturbations and nonlinearities of the object. Differently from all known approaches, there were used observers, which allow compensate observed errors from the first filter.